Conflict of character and resolution in animal stories - Abdul Rahman, Nadiatul Shakinah; Noor Muhammad, Salmah Jan; Jaffar, Siti Rabiatul Adawiah (Human Resource Management Academic Research Society, 2018)
Animal stories put forth the animal characters such as Sang Kancil, Sang Harimau, Sang Rusa and Sang Buaya as the characters that lead a life in the forest. Often times, these characters are portrayed as human beings that capable of speaking, thinking, articulating and doing things a human being used to do. Therefore, animal characters are also not escapable from having myriad of conflicts and problems as real human beings do. On the other note, animal stories are prone in displaying intelligent character such as Sang Kancil that has ecumenical ability to resolve problems and conflicts by the employment of diversified tricks to accomplish its goals. This paper will study two main focuses which are identifying and analyzing the applied mechanism by animal characters from Hikayat Sang Kancil and Kumpulan Cerita Sang Kancil as the research data. The methodology of this research employed the qualitative approaches that were library research and research data analysis. The meticulous analysis conducted revealed that an animal character that is Sang Kancil employed the flora and fauna elements as the mechanisms to solve problems and conflicts and the impacts were observable in the positive manner for each problem solved. Hence, humans are benefitted to observe examples and lessons from the animal intelligentsia in resolving conflicts and problems.